Development and Validation of the Nursing Information Security Questionnaire - Zhou, Xiaoyun; Jing, Xiujuan; Gao, Tingting; Liu, Hong; Jing, Xuebing (Applied Clinical Informatics, 2025)
Background Ensuring the security of nursing information holds substantial importance to nursing outcomes and healthcare system management. The awareness of information security among nurses in China is generally inadequate, and there is a lack of standardized evaluation tools for nurse information security in nursing practice. The nursing sector necessitates the establishment of a robust culture surrounding information security.Objective The aim of this study was to construct a self-reporting instrument for evaluating nursing information security.Methods The research team utilized literature analysis and group discussions to draft the item pool. After two rounds of Delphi consultation by 15 experts and pilot testing, the initial questionnaire was formed. Item analysis was carried out on the questionnaire, and the validity and reliability of the instrument were statistically tested by computing the Keiser–Meier–Olkin and Bartlett's tests, an exploratory factor analysis (EFA), a confirmatory factor analysis (CFA), convergent and discriminative validity, descriptive statistics, Cronbach's α, and test–retest reliability.Results A total of 501 nurses participated in the study, supplemented by the inclusion of five experts who were invited to contribute to the assessment of content validity. Four factors were formed using EFA (n = 250), and the cumulative variance contribution rate was found to be 60.10%. The CFA (n = 251) showed that the model fit was good. The overall Cronbach's α coefficient of the questionnaire was 0.948, and the test–retest reliability was 0.837.Conclusion Finally, the nursing information security questionnaire (NIS-Q) with 38 items and three dimensions of knowledge, attitude, and practice were formed. A promising assessment instrument for gauging the degree of nursing information security was introduced. Further, a foundational platform was established for implementing specific enhancement strategies aimed at advancing nursing information security.
Keywords: nursing; information security; knowledge; attitude and practice; validation; reliability